2017
DOI: 10.5688/ajpe6109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Residency School-wide Match Rates and Modifiable Predictors in ACPE-accredited Colleges and Schools of Pharmacy

Abstract: Objective. To analyze the modifiable predictors of institution-wide residency match rates. Methods. This was a retrospective analysis of colleges and schools of pharmacy data and school-wide PGY-1 pharmacy residency match rates for 2013 through 2015. Independent variables included NAPLEX passing rates, history of ACPE probation, NIH funding, academic health center affiliation, dual-degree availability, program length, admit-to-applicant ratio, class size, tuition, student-driven research, clinically focused ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Recently, Whittaker and colleagues examined modifiable predictors of institution-wide first-year postgraduate (PGY1) residency match rates among 121 colleges and schools of pharmacy and noted that average NAPLEX pass rate, academic health center affiliation, admit-to-applicant ratio, and U.S. News & World Report rankings positively predicted match rates, while larger class size and higher minority enrollment were significant negative predictors. 10 Beginning in 2015, the NAPLEX has undergone several changes, including a revision to the passing standard in 2015, and starting in 2016, extending the length of the examination from 4.25 hours to 6 hours, increasing the number of questions from 185 to 250, and moving from a computer adaptive format to a preassembled model with certain percentages of questions varying in difficulty. Most of the questions on the NAPLEX are scenariobased, using patient profiles or medical records that require analysis in order to answer related questions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Whittaker and colleagues examined modifiable predictors of institution-wide first-year postgraduate (PGY1) residency match rates among 121 colleges and schools of pharmacy and noted that average NAPLEX pass rate, academic health center affiliation, admit-to-applicant ratio, and U.S. News & World Report rankings positively predicted match rates, while larger class size and higher minority enrollment were significant negative predictors. 10 Beginning in 2015, the NAPLEX has undergone several changes, including a revision to the passing standard in 2015, and starting in 2016, extending the length of the examination from 4.25 hours to 6 hours, increasing the number of questions from 185 to 250, and moving from a computer adaptive format to a preassembled model with certain percentages of questions varying in difficulty. Most of the questions on the NAPLEX are scenariobased, using patient profiles or medical records that require analysis in order to answer related questions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of other factors were associated with higher match rates in individual studies, including the age of the school, 25 accreditation status, 22 number of funded faculty, 23 class size, 24 and minority enrollment 24 . Use of a numeric grading scale (vs pass/fail grading) was associated with a higher match rate in one study 7 but not when advanced pharmacy practice experiences were studied exclusively 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies compared school‐level factors with match rate; these studies were classified as biodata rather than academic performance because individual student performance was not assessed. Multiple studies demonstrated that match rates tended to be higher for 4‐year programs, 7,22 public institutions, 7,23 and schools affiliated with an academic medical center 23‐25 . Higher pass rates on the North American Pharmacist Licensure Examination (NAPLEX) were also associated with higher match rates 22‐24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations